High-activity in-situ crystallization catalyst as well as preparation method and application thereof

By increasing the silicon-aluminum ratio and crystallinity of NaY zeolite in the preparation process, the problem of low silicon-aluminum ratio of NaY zeolite in the prior art is solved, and the preparation of a high-active in situ crystallization catalyst is achieved, and its performance in heavy oil catalytic cracking is improved.

CN119838627APending Publication Date: 2025-04-18WEIFANG ZHENGXUAN RARE EARTH CATALYTIC MATERIALS CO LTD

Patent Information

Application Number
CN202510336245.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the silicon-aluminum ratio of NaY zeolite is relatively low, resulting in its hydrothermal activity that cannot meet the demand for the processing of inferior raw materials in the catalytic device.

Method used

By alkali treatment of high soil and mixing it with kaolin, and then calcined, in situ crystallization with silicon source, sodium hydroxide, seed crystal and silicon-aluminum activator, the silicon-aluminum ratio and crystallinity of NaY zeolite are improved, and a high-active in situ crystallization catalyst is prepared by ammonium salt, rare earth exchange and calcination and phosphorus or boron modification treatment.

Benefits of technology

The silicon-aluminum ratio and catalytic activity of the catalyst are improved, the heavy oil conversion and anti-metal pollution ability in heavy oil catalytic cracking are enhanced, and the total liquid collection is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838627A_ABST
    Figure CN119838627A_ABST
Patent Text Reader

Abstract

The invention provides a high-activity in-situ crystallization catalyst as well as a preparation method and application thereof, and belongs to the technical field of oil refining catalysts. The preparation method comprises the following steps: firstly, carrying out alkali treatment on kaolin, then mixing with kaolin to obtain modified kaolin microspheres, roasting, and then carrying out in-situ crystallization on the modified kaolin microspheres, a silicon source, sodium hydroxide, a seed crystal and a silicon-aluminum activator, so that the activation degree of silicon dioxide in kaolin is promoted, and meanwhile, timely insertion of active silicon species into a NaY zeolite skeleton in the crystallization process is accelerated; the high-activity in-situ crystallization catalyst is prepared by carrying out ammonium salt and rare earth exchange, roasting and phosphorus or boron modification treatment on the crystallized microspheres, and has the characteristics of strong heavy oil conversion and metal pollution resistance and high total liquid yield when catalyzing heavy oil cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil refining catalysts, and in particular relates to a high-activity in-situ crystallization catalyst and a preparation method and application thereof. Background Art

[0002] In-situ crystallized catalytic cracking catalysts play an important role in the deep conversion process of heavy oil due to their well-developed pore structure, good hydrothermal stability, and strong resistance to metal pollution. This type of catalyst is made by mixing kaolin-based clay, beating it, spraying it to form microspheres, and synthesizing NaY zeolite through high-temperature activation and hydrothermal treatment, and then undergoing ion exchange, filtration, roasting and other processes. As the processing raw materials of some domestic refineries become heavier and inferior, the content of heavy metals such as vanadium and nickel, as well as colloids and asphaltene has increased sharply, which has put forward higher requirements on the performance of heavy oil catalytic cracking catalysts. At present, a prominent problem in the preparation of in-situ crystallized heavy oil catalytic cracking catalysts is that the silicon-aluminum ratio of the synthesized NaY zeolite is low, resulting in its hydrothermal activity not being able to meet the needs of catalytic devices for processing inferior raw materials.

[0003] Therefore, how to increase the silicon-to-aluminum ratio of NaY zeolite and simultaneously improve its catalytic activity becomes a difficult problem in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a high-activity in-situ crystallization catalyst and its preparation method and application. The catalyst prepared by the present invention has a high silicon-aluminum ratio and excellent catalytic activity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a high-activity in-situ crystallization catalyst, comprising the following steps: (1) mixing kaolin with alkali solution and water, adding kaolin, silicon-aluminum activator and dispersant after alkali treatment to obtain modified kaolin slurry, and spray drying to obtain modified kaolin microspheres; (2) calcining the modified kaolin microspheres obtained in step (1) to obtain calcined kaolin microspheres; (3) mixing the calcined soil balls obtained in step (2) with water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-aluminum activator to carry out an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (4) mixing the NaY zeolite crystallized microspheres obtained in step (3) with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (5) mixing the ammonium salt exchange microspheres obtained in step (4) with a rare earth salt and water, and sequentially performing a first rare earth exchange and a first calcination to obtain primary rare earth exchange microspheres; (6) mixing the primary rare earth exchange microspheres obtained in step (5) with rare earth salt and water, and sequentially performing a second rare earth exchange and a second calcination to obtain secondary rare earth exchange microspheres; (7) The secondary rare earth exchange microspheres obtained in step (6), water and a phosphorus compound or a boron compound are mixed and modified to obtain a highly active in-situ crystallization catalyst.

[0006] Preferably, the alkali solution in step (1) comprises a sodium hydroxide solution; and the mass ratio of sodium hydroxide to kaolin in the sodium hydroxide solution is 0.02-0.25.

[0007] Preferably, the temperature of the alkali treatment in step (1) is 30-95° C., and the time of the alkali treatment is 0.5-10 h.

[0008] Preferably, in step (1), the mass ratio of kaolinite to kaolin is (1-5):(1-6); and the mass ratio of the total mass of kaolinite and kaolin to the mass of the silica-alumina activator and the dispersant is 100:(0.5-12):(2-12).

[0009] Preferably, the calcination temperature in step (2) is 700-900° C., and the calcination time is 1-5 h.

[0010] Preferably, the temperature of the in-situ crystallization synthesis reaction in step (3) is 90-110° C., and the time of the in-situ crystallization synthesis reaction is 16-40 hours.

[0011] Preferably, in step (4), the pH value of the ammonium salt exchange is 2.5-4, the temperature of the ammonium salt exchange is 30-100° C., and the time of the ammonium salt exchange is 0.5-4 h.

[0012] Preferably, the pH value of the modification treatment in step (7) is 2.5-4, the temperature of the modification treatment is 40-100° C., and the time of the modification treatment is 0.5-4 h.

[0013] The present invention also provides a high-activity in-situ crystallization catalyst prepared by the preparation method described in the above technical solution.

[0014] The present invention also provides the use of the high-activity in-situ crystallization catalyst described in the above technical solution in heavy oil catalytic cracking.

[0015] The present invention provides a method for preparing a high-activity in-situ crystallization catalyst, comprising the following steps: (1) mixing kaolin with alkali solution and water, performing alkali treatment, adding kaolin, a silicon-aluminum activator and a dispersant to obtain a modified kaolin slurry, and spray drying to obtain modified kaolin microspheres; (2) calcining the modified kaolin microspheres obtained in step (1) to obtain calcined kaolin balls; (3) mixing the calcined kaolin balls obtained in step (2) with water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-aluminum activator to perform an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (4) treating the kaolin obtained in step (3) with water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-aluminum activator to obtain a NaY zeolite crystallized microsphere. The NaY zeolite crystallized microspheres are mixed with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (5) the ammonium salt exchange microspheres obtained in step (4) are mixed with rare earth salt and water, and a first rare earth exchange and a first calcination are performed in sequence to obtain primary rare earth exchange microspheres; (6) the primary rare earth exchange microspheres obtained in step (5) are mixed with rare earth salt and water, and a second rare earth exchange and a second calcination are performed in sequence to obtain secondary rare earth exchange microspheres; (7) the secondary rare earth exchange microspheres obtained in step (6), water and a phosphorus compound or a boron compound are mixed, and a modification treatment is performed to obtain a high-activity in-situ crystallization catalyst. The present invention firstly treats the kaolin with alkali, and then mixes it with kaolin to obtain modified kaolin microspheres, and then performs in-situ crystallization with a silicon source, sodium hydroxide, a crystal seed and a silicon-aluminum activator after calcination, which not only promotes the activation degree of silicon dioxide in kaolin, but also accelerates the timely insertion of active silicon species into the NaY zeolite framework during the crystallization process, improves the silicon-aluminum ratio and crystallinity of the crystallized microspheres, and then performs ammonium salt, rare earth exchange and calcination and phosphorus or boron modification treatment to prepare a high-activity in-situ crystallization catalyst, which has the characteristics of strong heavy oil conversion and anti-metal pollution ability and high total liquid yield when catalyzing heavy oil cracking. The results of the embodiment show that the catalyst prepared by the present invention has an activity retention rate of more than 85% after being contaminated by 8000ppm vanadium and 4000ppm nickel, and when catalyzing heavy oil cracking, the conversion rate is more than 79%, and the total liquid yield is more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD pattern of NaY zeolite crystallized microspheres JM-6 prepared in step (3) of Example 6; Figure 2 This is a SEM image of NaY zeolite crystallized microspheres JM-6 prepared in step (3) of Example 6; Figure 3 This is a SEM image of the surface of NaY zeolite crystallized microsphere JM-6 prepared in step (3) of Example 6; Figure 4 The XRD pattern of the crystallized microsphere DJM prepared in step (1) of comparative example 1; Figure 5 This is a SEM image of the crystallized microsphere DJM prepared in step (1) of Comparative Example 1; Figure 6 This is a SEM image of the surface of the crystallized microsphere DJM prepared in step (1) of comparative example 1. DETAILED DESCRIPTION

[0017] The present invention provides a method for preparing a high-activity in-situ crystallization catalyst, comprising the following steps: (1) mixing kaolin with alkali solution and water, adding kaolin, silicon-aluminum activator and dispersant after alkali treatment to obtain modified kaolin slurry, and spray drying to obtain modified kaolin microspheres; (2) calcining the modified kaolin microspheres obtained in step (1) to obtain calcined kaolin microspheres; (3) mixing the calcined soil balls obtained in step (2) with water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-aluminum activator to carry out an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (4) mixing the NaY zeolite crystallized microspheres obtained in step (3) with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (5) mixing the ammonium salt exchange microspheres obtained in step (4) with a rare earth salt and water, and sequentially performing a first rare earth exchange and a first calcination to obtain primary rare earth exchange microspheres; (6) mixing the primary rare earth exchange microspheres obtained in step (5) with rare earth salt and water, and sequentially performing a second rare earth exchange and a second calcination to obtain secondary rare earth exchange microspheres; (7) The secondary rare earth exchange microspheres obtained in step (6), water and a phosphorus compound or a boron compound are mixed and modified to obtain a highly active in-situ crystallization catalyst.

[0018] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and any commercially available product or product prepared by a conventional preparation method well known to those skilled in the art may be used.

[0019] The invention mixes kaolin with alkali solution and water, performs alkali treatment, and then adds kaolin, silicon-aluminum activator and dispersant to obtain modified kaolin slurry, which is spray-dried to obtain modified kaolin microspheres.

[0020] In the present invention, the kaolin is preferably at least one of calcined kaolin, halloysite and coal gangue. In the present invention, the calcination temperature is preferably 900-1100°C; the calcination time is preferably 1-5h. In an embodiment of the present invention, the calcination temperature may be specifically 900°C, 950°C, 1000°C, 1050°C or 1100°C; the calcination time may be specifically 1h, 2h, 3h, 4h or 5h. The present invention controls the calcination temperature and time within the above range, which can further improve the catalytic performance of the catalyst.

[0021] In the present invention, the average particle size of the high soil is preferably 1.5-5.0 μm. In an embodiment of the present invention, the average particle size of the high soil can be specifically 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm.

[0022] In the present invention, the alkali solution preferably comprises a sodium hydroxide solution; calculated as sodium oxide, the mass content of sodium oxide in the sodium hydroxide solution is preferably 15-17%, more preferably 16%.

[0023] In the present invention, the mass ratio of sodium hydroxide to high soil in the sodium hydroxide solution is preferably 0.02 to 0.25. In an embodiment of the present invention, the mass ratio of sodium hydroxide to high soil in the sodium hydroxide solution can be specifically 0.02, 0.05, 0.08, 0.10, 0.15, 0.18, 0.20, 0.22 or 0.25.

[0024] In the present invention, the liquid-to-solid ratio of the high soil when mixed with alkali solution and water is preferably 2-5 L / g. In an embodiment of the present invention, the liquid-to-solid ratio of the high soil when mixed with alkali solution and water can be specifically 2 L / g, 3 L / g, 4 L / g, or 5 L / g.

[0025] The present invention has no special limitation on the operation of mixing the high-quality soil, alkali solution and water, and a technical solution for mixing materials well known to those skilled in the art can be adopted.

[0026] In the present invention, the temperature of the alkali treatment is preferably 30-95° C. In an embodiment of the present invention, the temperature of the alkali treatment may be specifically 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C. or 95° C.

[0027] In the present invention, the alkali treatment time is preferably 0.5 to 10 hours. In an embodiment of the present invention, the alkali treatment time can be specifically 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.

[0028] In the present invention, the alkali treatment can extract part of the active silica in the high soil from the solid phase into the liquid phase. The present invention controls the parameters such as the amount of each raw material, the reaction temperature and the time within the above range, which can further improve the crystallinity of the crystallized product.

[0029] After the alkali treatment is completed, the present invention adds kaolin, a silicon-aluminum activator and a dispersant to obtain a modified kaolin slurry, which is spray-dried to obtain modified kaolin microspheres.

[0030] In the present invention, the kaolin is preferably uncalcined common kaolin or halloysite; the average particle size of the kaolin is preferably 1.5 to 5.0 μm. In an embodiment of the present invention, the average particle size of the kaolin may be specifically 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm.

[0031] In the present invention, the molar ratio of Na2O, Al2O3, SiO2 and H2O in the silicon-aluminum activator is preferably (1-50):1:(1-60):(10-360).

[0032] In the present invention, the method for preparing the silicon-aluminum activator is preferably: a silicon source, an aluminum source and water are mixed and then aged to obtain the silicon-aluminum activator.

[0033] In the present invention, the silicon source preferably includes at least one of water glass, silica sol, white carbon black, silica gel and silicon-containing crystallization mother liquor. The present invention has no special limitation on the source of the silicon source, and commercially available products known to those skilled in the art can be used. In an embodiment of the present invention, the mass content of silicon dioxide in the water glass is 20%; the mass content of silicon dioxide in the silica sol is 30%; the mass content of silicon dioxide in the white carbon black is 99%; the silicon-containing crystallization mother liquor is a zeolite crystallization mother liquor; the mass content of silicon dioxide in the zeolite crystallization mother liquor is 12%.

[0034] In the present invention, the aluminum source preferably includes at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, pseudo-boehmite, boehmite and aluminum chloride.

[0035] In the present invention, the mixing of the silicon source, the aluminum source and water is preferably performed by mixing the aluminum source and water to obtain an aluminum source solution, which is then mixed with the silicon source.

[0036] In the present invention, the mass concentration of aluminum oxide in the aluminum source solution is preferably 5-15% in terms of aluminum oxide. In an embodiment of the present invention, the mass concentration of aluminum oxide in the aluminum source solution may be specifically 5%, 6%, 7%, 8%, 9%, 10%, 12% or 15%.

[0037] In the present invention, the aging temperature is preferably 30-95° C. In an embodiment of the present invention, the aging temperature may be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 95° C.

[0038] In the present invention, the aging time is preferably 5 to 30 hours. In the present invention, the aging time can be specifically 5 hours, 10 hours, 15 hours, 20 hours, 25 hours or 30 hours. The present invention controls the aging temperature and time within the above range, so that the raw materials can fully react.

[0039] In the present invention, the dispersant preferably includes at least one of water glass, orthophosphoric acid, metaphosphoric acid, polyacrylamide and sodium polyacrylate.

[0040] In the present invention, the mass ratio of kaolinite to kaolin is preferably (1-5): (1-6). In an embodiment of the present invention, the mass ratio of kaolinite to kaolin may specifically be: 1.5:3.5, 2:3, 1:1 or 3:2.

[0041] In the present invention, the mass ratio of the total mass of the kaolinite and kaolin to the silica-alumina activator and dispersant is preferably 100:(0.5-12):(2-12). In an embodiment of the present invention, the mass ratio of the total mass of the kaolinite and kaolin to the silica-alumina activator and dispersant can be specifically 100:5:2, 100:3:6, 100:12:4.5 or 100:8:8.

[0042] In the present invention, the solid content of the modified kaolin slurry is preferably 28-50%.

[0043] In the present invention, when the solid content of the modified kaolin slurry is not within the above range, water is preferably added. The present invention has no particular limitation on the amount of water, as long as the solid content of the modified kaolin slurry is within the above range.

[0044] The present invention controls the mass ratio and solid content of each component within the above range, which can make the raw materials mixed more uniformly and further improve the catalytic performance of the catalyst.

[0045] In the present invention, the main particle size of the modified kaolin microspheres is preferably 20-150 μm, that is, the volume fraction of microspheres with a particle size within the range of 20-150 μm accounts for ≥90%.

[0046] The present invention has no special limitation on the spray drying operation, and a technical solution well known to those skilled in the art can be used to ensure that the particle size of the modified kaolin microspheres is within the above range.

[0047] After obtaining the modified kaolin microspheres, the present invention calcines the modified kaolin microspheres to obtain calcined kaolin microspheres.

[0048] In the present invention, the calcination temperature is preferably 700-900° C. In an embodiment of the present invention, the calcination temperature may be specifically 700° C., 750° C., 800° C., 850° C. or 900° C.

[0049] In the present invention, the calcination time is preferably 1 to 5 hours. In an embodiment of the present invention, the calcination time may be specifically 1 hour, 2 hours, 3 hours, 4 hours or 5 hours. In the present invention, the aluminum source in the modified kaolin microspheres is fully activated during the calcination process. The present invention controls the calcination temperature and time within the above range, which can further improve the crystallization efficiency and crystallization degree of the activated silicon source and aluminum source.

[0050] After obtaining the calcined soil balls, the present invention mixes the calcined soil balls with water, silicon source, sodium hydroxide solution, crystal seeds and silicon-aluminum activator to carry out in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres.

[0051] In the present invention, the silicon source is preferably water glass.

[0052] In the present invention, the mass content of sodium oxide in the sodium hydroxide solution is preferably 15-17%, more preferably 16%, calculated as sodium oxide.

[0053] In the present invention, the seed crystal is preferably a Y-type molecular sieve; the molar ratio of silicon dioxide to aluminum oxide in the Y-type molecular sieve is preferably ≥15.

[0054] In the present invention, the silicon-aluminum activator is preferably the same as the above-mentioned silicon-aluminum activator, which will not be described in detail here.

[0055] In the present invention, the mass ratio of the calcined clay ball, Na2O, SiO2, seed, silica-alumina activator and water in the mixed system obtained by mixing the calcined clay ball with water, silicon source, sodium hydroxide, seed and silica-alumina activator is preferably 100: (10-35): (15-60): (1-15): (5-45): (250-600). In the present invention, the Na2O is the total mass of sodium hydroxide (in terms of Na2O) and Na2O in water glass.

[0056] In the present invention, the mass ratio of the calcined soil ball to the silicon source, the sodium hydroxide solution, the seed crystal, the silicon-aluminum activator and water is preferably 100: (200-400): (150-300): (2-5): (50-100): (10-50). In an embodiment of the present invention, the mass ratio of the calcined soil ball to the silicon source, the sodium hydroxide solution, the seed crystal, the silicon-aluminum activator and the water can be specifically: 100:210:200:2:70:20, 100:250:210:2.2:60:50, 100:350:190:4.8:90:30, 100:300:180:2.8:82:45, 100:280:240:3.5:83:30, 100:330:250:3.8:85:40, 100:320:230:4.5:78:50 or 100:270:210:4.4:79:40. The present invention controls the mass ratio of each component within the above range, which can further improve the silicon-aluminum ratio and crystallinity of the NaY zeolite crystallized microspheres, thereby improving the catalytic performance of the catalyst.

[0057] The present invention has no special limitation on the operation of mixing the calcined soil ball with water, silicon source, sodium hydroxide solution, seed crystal and silicon-aluminum activator, and the technical scheme of material mixing well known to those skilled in the art can be adopted.

[0058] In the present invention, the calcined soil ball is preferably aged after being mixed with water, silicon source, sodium hydroxide solution, seed crystal and silicon-aluminum activator, and then subjected to in-situ crystallization synthesis reaction.

[0059] In the present invention, the aging temperature is preferably 30-80° C.; the aging time is preferably 0.1-20 h.

[0060] In the present invention, the temperature of the in-situ crystallization synthesis reaction is preferably 90-110° C. In an embodiment of the present invention, the temperature of the in-situ crystallization synthesis reaction can be specifically 90° C., 95° C., 100° C., 105° C. or 110° C.

[0061] In the present invention, the time of the in-situ crystallization synthesis reaction is preferably 16 to 40 hours. In an embodiment of the present invention, the time of the in-situ crystallization synthesis reaction may be specifically 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours or 40 hours. The present invention controls the temperature and time of the in-situ crystallization synthesis reaction within the above range, so that the reaction can be fully carried out, further improve the silicon-aluminum ratio and crystallinity of the NaY zeolite crystallized microspheres, and then improve the catalytic performance of the catalyst.

[0062] After the in-situ crystallization synthesis reaction is completed, the product of the in-situ crystallization synthesis reaction is preferably filtered, washed and dried in sequence to obtain NaY zeolite crystallized microspheres.

[0063] The present invention has no special limitation on the filtering, washing and drying operations, and the technical solutions well known to those skilled in the art can be adopted.

[0064] In the present invention, the mass content of NaY zeolite in the NaY zeolite crystallized microspheres is preferably 50-70%; the molar ratio of silicon to aluminum in the NaY zeolite crystallized microspheres is preferably 5.0-6.1.

[0065] After obtaining the NaY zeolite crystallized microspheres, the present invention mixes the NaY zeolite crystallized microspheres with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchanged microspheres.

[0066] In the present invention, the ammonium salt preferably includes at least one of ammonium chloride, ammonium sulfate, ammonium nitrate and ammonium phosphate.

[0067] In the present invention, the mass ratio of the ammonium salt to the NaY zeolite crystallized microspheres is preferably 0.15 to 0.6. In an embodiment of the present invention, the mass ratio of the ammonium salt to the NaY zeolite crystallized microspheres may be specifically 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 or 0.6.

[0068] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 10 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres may specifically be 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g or 10 L / g.

[0069] In the present invention, the pH value of the ammonium salt exchange is preferably 2.5 to 4. In an embodiment of the present invention, the pH value of the ammonium salt exchange can be specifically 2.5, 3.0, 3.5 or 4.0.

[0070] In the present invention, the temperature of the ammonium salt exchange is preferably 30-100° C. In an embodiment of the present invention, the temperature of the ammonium salt exchange may be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0071] In the present invention, the time for the ammonium salt exchange is preferably 0.5 to 4 hours. In an embodiment of the present invention, the time for the ammonium salt exchange can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0072] The present invention controls the dosage of each component, the reaction temperature and the reaction time within the above ranges, so that the reaction can proceed fully.

[0073] After the ammonium salt exchange is completed, the present invention preferably filters and washes the ammonium salt exchange product in sequence to obtain ammonium salt exchange microspheres.

[0074] The present invention has no special limitation on the filtering and washing operations, and the filtering and washing technical solutions well known to those skilled in the art can be adopted.

[0075] After obtaining the ammonium salt exchange microspheres, the present invention mixes the ammonium salt exchange microspheres with rare earth salt and water, and sequentially performs a first rare earth exchange and a first calcination to obtain primary rare earth exchange microspheres.

[0076] In the present invention, the rare earth salt preferably includes at least one of rare earth hydrochlorides, rare earth nitrates and rare earth carbonates; the rare earth in the rare earth salt preferably includes at least one of La, Ce, Pr, Y and Sc.

[0077] In the present invention, the rare earth in the rare earth salt is preferably La and Ce, and the mass ratio of lanthanum oxide to cerium oxide in the rare earth salt is preferably (2-3):1, calculated as lanthanum oxide and cerium oxide.

[0078] In the present invention, the rare earth salt is calculated as rare earth oxide, and the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres is preferably 0.02 to 0.06. In an embodiment of the present invention, the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres can be specifically 0.02, 0.03, 0.04, 0.05 or 0.06.

[0079] In the present invention, the ammonium salt exchange microspheres are preferably mixed with the rare earth salt and water by mixing the rare earth salt and part of the water to obtain a rare earth salt solution, which is then mixed with the ammonium salt exchange microspheres and the remaining water.

[0080] In the present invention, the rare earth salt is calculated as rare earth oxide, and the concentration of the rare earth oxide in the rare earth salt solution is preferably 240-270 g / L. The present invention has no special limitation on the amount of the water, as long as the concentration of the rare earth oxide in the rare earth salt solution is within the above range.

[0081] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 10 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres may specifically be 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g or 10 L / g.

[0082] In the present invention, the pH value of the first rare earth exchange is preferably 3 to 5. In an embodiment of the present invention, the pH value of the first rare earth exchange can be specifically 3, 3.5, 4, 4.5 or 5.

[0083] In the present invention, the temperature of the first rare earth exchange is preferably 30-100° C. In an embodiment of the present invention, the temperature of the first rare earth exchange can be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0084] In the present invention, the time for the first rare earth exchange is preferably 0.5 to 4 hours. In an embodiment of the present invention, the time for the first rare earth exchange can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0085] The present invention controls the dosage of each component, the reaction temperature and the reaction time within the above ranges, so that the reaction can proceed fully.

[0086] After the first rare earth exchange is completed, the present invention preferably filters and washes the product of the first rare earth exchange in sequence, and then performs a first calcination.

[0087] The present invention has no special limitation on the filtering and washing operations, and the filtering and washing technical solutions well known to those skilled in the art can be adopted.

[0088] In the present invention, the temperature of the first calcination is preferably 450-700° C. In an embodiment of the present invention, the temperature of the first calcination may specifically be 450° C., 500° C., 550° C., 600° C., 650° C. or 700° C.

[0089] In the present invention, the first calcination time is preferably 0.5 to 4 hours. In an embodiment of the present invention, the first calcination time can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0090] In the present invention, the first calcination is preferably carried out under air or water vapor conditions. In the present invention, the volume percentage of the water vapor is preferably 10 to 50%. The present invention controls the parameters such as the amount of each component, reaction temperature and time within the above range, which can allow more rare earths to be exchanged and further improve the catalytic performance of the catalyst.

[0091] After obtaining the primary rare earth exchange microspheres, the present invention mixes the primary rare earth exchange microspheres with rare earth salt and water, and sequentially performs a second rare earth exchange and a second calcination to obtain secondary rare earth exchange microspheres.

[0092] In the present invention, the rare earth salt preferably includes at least one of rare earth hydrochlorides, rare earth nitrates and rare earth carbonates; the rare earth in the rare earth salt preferably includes at least one of La, Ce, Pr, Y and Sc.

[0093] In the present invention, the rare earth in the rare earth salt is preferably La and Ce, and the mass ratio of lanthanum oxide to cerium oxide in the rare earth salt is preferably (2-3):1, calculated as lanthanum oxide and cerium oxide.

[0094] In the present invention, the rare earth salt is calculated as rare earth oxide, and the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres is preferably 0.02 to 0.06. In an embodiment of the present invention, the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres can be specifically 0.02, 0.03, 0.04, 0.05 or 0.06.

[0095] In the present invention, the mixing of the primary rare earth exchange microspheres with the rare earth salt and water is preferably: the rare earth salt is mixed with part of the water to obtain a rare earth salt solution, which is then mixed with the primary rare earth exchange microspheres and the remaining water.

[0096] In the present invention, the rare earth salt is calculated as rare earth oxide, and the concentration of the rare earth oxide in the rare earth salt solution is preferably 240-270 g / L. The present invention has no special limitation on the amount of the water, as long as the concentration of the rare earth oxide in the rare earth salt solution is within the above range.

[0097] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 10 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres may specifically be 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g or 10 L / g.

[0098] In the present invention, the pH value of the second rare earth exchange is preferably 3 to 5. In an embodiment of the present invention, the pH value of the second rare earth exchange can be specifically 3, 3.5, 4, 4.5 or 5.

[0099] In the present invention, the temperature of the second rare earth exchange is preferably 30-100° C. In an embodiment of the present invention, the temperature of the second rare earth exchange can be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0100] In the present invention, the second rare earth exchange time is preferably 0.5 to 4 hours. In an embodiment of the present invention, the second rare earth exchange time can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0101] The present invention controls the dosage of each component, the reaction temperature and the reaction time within the above ranges, so that the reaction can proceed fully.

[0102] After the second rare earth exchange is completed, the present invention preferably filters and washes the product of the second rare earth exchange in sequence, and then performs a second calcination.

[0103] The present invention has no special limitation on the filtering and washing operations, and the filtering and washing technical solutions well known to those skilled in the art can be adopted.

[0104] In the present invention, the temperature of the second calcination is preferably 500-750° C. In an embodiment of the present invention, the temperature of the second calcination may specifically be 500° C., 550° C., 600° C., 650° C., 700° C. or 750° C.

[0105] In the present invention, the second calcination time is preferably 0.5 to 4 hours. In an embodiment of the present invention, the second calcination time can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0106] In the present invention, the second calcination is preferably carried out under air or water vapor conditions. In the present invention, the volume percentage of the water vapor is preferably 10 to 50%. The present invention controls the parameters such as the amount of each component, reaction temperature and time within the above range, which can allow more rare earths to be exchanged and further improve the catalytic performance of the catalyst.

[0107] After obtaining the secondary rare earth exchange microspheres, the present invention mixes the secondary rare earth exchange microspheres, water and a phosphorus compound or a boron compound, performs a modification treatment, and obtains a high-activity in-situ crystallization catalyst.

[0108] In the present invention, the phosphorus compound preferably includes at least one of ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, pyrophosphoric acid and metaphosphoric acid.

[0109] In the present invention, the boron compound preferably includes at least one of boric acid and ammonium borate.

[0110] In the present invention, the mass ratio of the phosphorus compound or boron compound to the NaY zeolite crystallized microspheres is preferably 0.005 to 0.2. In an embodiment of the present invention, the mass ratio of the phosphorus compound or boron compound to the NaY zeolite crystallized microspheres can be specifically 0.005, 0.01, 0.05, 0.1, 0.15 or 0.2.

[0111] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 9 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres can be specifically 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g or 9 L / g.

[0112] In the present invention, the pH value of the modification treatment is preferably 2.5 to 4. In an embodiment of the present invention, the pH value of the modification treatment may specifically be 2.5, 3, 3.5 or 4.

[0113] In the present invention, the temperature of the modification treatment is preferably 40-100° C. In an embodiment of the present invention, the temperature of the modification treatment may specifically be 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0114] In the present invention, the time of the modification treatment is preferably 0.5 to 4 hours. In an embodiment of the present invention, the time of the modification treatment may be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours. The present invention controls the amount of each component, the reaction temperature and the time within the above range, so that the modification treatment can be more sufficient and the catalytic performance of the catalyst can be further improved.

[0115] After the modification treatment is completed, the present invention preferably filters, washes and dries the modified product in sequence to obtain a highly active in-situ crystallization catalyst.

[0116] The present invention has no special limitation on the filtering, washing and drying operations, and the technical solutions well known to those skilled in the art can be adopted.

[0117] The invention firstly performs alkali treatment on kaolinite, and then mixes the kaolinite with kaolinite to obtain modified kaolinite microspheres. After calcination, the kaolinite is in-situ crystallized with a silicon source, sodium hydroxide, a crystal seed and a silicon-aluminum activator, which not only promotes the activation degree of silicon dioxide in the kaolinite, but also accelerates the active silicon species in the crystallization process to be inserted into the NaY zeolite framework in time, thereby improving the silicon-aluminum ratio and crystallinity of the crystallized microspheres. Then, the kaolinite is subjected to ammonium salt and rare earth exchange and calcination and phosphorus or boron modification treatment. After the ammonium salt and rare earth exchange and calcination and modification treatment, the micro-reaction activity and hydrothermal stability thereof are greatly improved, the catalytic performance of the catalyst is further improved, and the process parameters such as the amount of each component, the reaction temperature and the time are controlled to prepare a high-activity in-situ crystallization catalyst.

[0118] The present invention also provides a high-activity in-situ crystallization catalyst prepared by the preparation method described in the above technical solution.

[0119] The present invention also provides the use of the high-activity in-situ crystallization catalyst described in the above technical solution in heavy oil catalytic cracking.

[0120] The high-activity in-situ crystallization catalyst of the present invention can be used for processing various raw materials, including paraffin-based, cycloalkyl-based, intermediate-based wax oils and blended residual oil raw materials.

[0121] In the present invention, the temperature of the catalytic cracking is preferably 400-700°C, more preferably 450-650°C; during the catalytic cracking, the mass ratio of the catalyst to the heavy oil is preferably 3-25, more preferably 4-22.

[0122] The catalyst prepared by the invention has excellent catalytic performance, and has the characteristics of strong heavy oil conversion and metal pollution resistance and high total liquid yield when catalyzing heavy oil cracking.

[0123] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0124] The specifications, compositions or preparation methods of the raw materials in the embodiments and comparative examples are as follows: Kaolin, solid content 85.8%, Fe2O3 0.3wt%, TiO2 0.2wt%, average particle size 3.5μm.

[0125] Halloysite (haywater kaolinite), solid content 86.4%, Fe2O3 1.1wt%, TiO2 2.5wt%, average particle size 2.1μm.

[0126] The average particle size of coal gangue is 2.7μm.

[0127] 1# seed crystal, USY silicon-aluminum ratio is 25; 2# seed crystal, USY silicon-aluminum ratio is 15.

[0128] Zeolite crystallization mother liquor, SiO2 12wt%.

[0129] Directing agent: 15SiO2:Al2O3:15Na2O:320H2O (ratio of moles of substance).

[0130] Water glass, SiO2 content 20wt%; silica sol, SiO2 content 30wt%; white carbon black, SiO2 99wt%.

[0131] Sodium aluminate, Al2O3 content 7wt%, aluminum sulfate, Al2O3 content 12wt%, sodium hydroxide solution, Na2O content 16wt%.

[0132] Hydrochloric acid 36wt%; phosphoric acid 85wt%; phosphorous acid, chemically pure; sulfuric acid 98wt%.

[0133] The rare earth chloride solution, calculated as rare earth oxide, has a rare earth oxide concentration of 265 g / L; the rare earth nitric acid solution, calculated as rare earth oxide, has a rare earth oxide concentration of 242 g / L.

[0134] 1000 mL of water glass (SiO2 20 wt%) and 300 mL of aluminum sulfate (Al2O3 10 wt%) aqueous solution were mixed evenly and reacted at 50 °C for 15 h to obtain the silica-alumina activator SA-1. The molar ratio of Na2O, Al2O3, SiO2 and H2O was 5:1:13:196.

[0135] 800 mL of silica sol (SiO2 30 wt%) and 500 mL of sodium aluminate (Al2O3 7 wt%) aqueous solution were mixed evenly and reacted at 70 °C for 10 h to obtain silica-alumina activator SA-2. The molar ratio of Na2O, Al2O3, SiO2 and H2O was 4.9:1:10.6:29.

[0136] 1500mL of zeolite crystallization mother liquor (SiO2 12w%) and 250mL of aluminum sulfate (Al2O3 12w%) aqueous solution were mixed evenly and reacted at 90℃ for 5h to obtain silicon-aluminum activator SA-3. The molar ratio of Na2O, Al2O3, SiO2 and H2O was 4:1:7.1:197.

[0137] The kaolin fine powder was roasted at 950℃ for 3h to obtain 1# kaolin; the coal gangue fine powder was roasted at 980℃ for 2h to obtain 2# kaolin.

[0138] Example 1 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 7000g of water, 1000g of sodium hydroxide solution (Na2O16wt%) and 3000g of 1# kaolin are mixed (the mass ratio of sodium hydroxide to 1# kaolin in the sodium hydroxide solution is 0.069, and the liquid-to-solid ratio of 1# kaolin, sodium hydroxide solution and water is 2.6L / g), and the mixture is reacted at 75°C for 2h, and then kaolin, water glass, silica-alumina activator SA-1 and water are added (the mass ratio of 1# kaolin to kaolin is 1.5:1, and the mass ratio of the total mass of 1# kaolin and kaolin to water glass and silica-alumina activator SA-1 is 100:2:5) to prepare a modified kaolin slurry with a solid content of 35%, and spray-dry to obtain 4900g of modified kaolin microspheres with a main particle size of 20-150μm, which are recorded as TM1; (2) The modified kaolin microspheres were calcined at 760 °C for 3 h to obtain calcined clay balls, which were designated as HM1-1. (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystal and silica-alumina activator SA-1 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 1# seed crystal, silica-alumina activator SA-1 and water was 100:210:200:2:70:20), and an in-situ crystallization synthesis reaction was carried out at 98°C for 27h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-1. (4) 1000 g of NaY zeolite crystallized microspheres, 390 g of ammonium chloride and 5000 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.39, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5 L / g), the pH value was adjusted to 3.2, exchange was performed at 95 °C for 1.5 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides and NaY The mass ratio of zeolite crystallized microspheres is 0.05, the rare earth elements in rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide and cerium oxide in rare earth chloride is 2:1, the total volume of water in deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.5, exchanged at 95°C for 1h, filtered and washed to obtain a "second exchange" wet cake, calcined at 600°C for 2.5h to obtain a primary rare earth exchange microsphere, and water and A rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted the pH value to 3.2, exchanged at 85℃ for 1h, filtered and washed to obtain "tri-crosslinked The wet filter cake was calcined at 600°C for 2.5h to obtain secondary rare earth exchange microspheres; 4500g of water and 100g of ammonium phosphate (the mass ratio of ammonium phosphate to NaY zeolite crystallized microspheres was 0.10, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres was 4.5L / g) were added to the secondary rare earth exchange microspheres, mixed evenly, the pH value was adjusted to 2.8, and the catalyst was modified at 85°C for 1h, filtered, washed and dried to obtain a high-activity in-situ crystallized catalyst, recorded as JC-1, and the rare earth oxide content was 7.2wt% and P 1.5wt% after analysis.

[0139] Example 2 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 7000g of water, 1000g of sodium hydroxide solution (Na2O16wt%) and 3000g of 1# kaolin are mixed (the mass ratio of sodium hydroxide to 1# kaolin in the sodium hydroxide solution is 0.069, and the liquid-to-solid ratio of 1# kaolin, sodium hydroxide solution and water is 2.6L / g), and the mixture is reacted at 75°C for 2h, and then kaolin, water glass, silica-alumina activator SA-1 and water are added (the mass ratio of 1# kaolin to kaolin is 1.5:1, and the mass ratio of the total mass of 1# kaolin and kaolin to water glass and silica-alumina activator SA-1 is 100:2:5) to prepare a modified kaolin slurry with a solid content of 35%, and spray-dry to obtain 4900g of modified kaolin microspheres with a main particle size of 20-150μm, which are recorded as TM1; (2) calcining the modified kaolin microspheres at 800 °C for 1.5 h to obtain calcined clay balls, which are denoted as HM1-2; (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 2# seed crystal and silica-alumina activator SA-2 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 2# seed crystal, silica-alumina activator SA-2 and water was 100:250:210:2.2:60:50), and an in-situ crystallization synthesis reaction was carried out at 98°C for 20h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-2. (4) 1000 g of NaY zeolite crystallized microspheres, 390 g of ammonium chloride and 5000 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.39, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5 L / g), the pH value was adjusted to 3.2, exchange was performed at 95°C for 1.5 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L) were added to the "one-cross" filter cake. The mass ratio of oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in rare earth chloride are lanthanum and cerium, and the mass ratio of lanthanum oxide to cerium oxide in rare earth chloride is 2:1, and the mass ratio of the total volume of water in deionized water and rare earth chloride aqueous solution to NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.5, exchanged at 95°C for 1h, filtered and washed to obtain a "secondary exchange" wet cake, which was calcined at 600°C for 2.5h to obtain primary rare earth exchange microspheres. Add water and rare earth chloride aqueous solution to the primary rare earth exchange microspheres (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265 g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, and the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5 L / g), mix well, and adjust the pH value to 3.2 , exchange at 85℃ for 1h, filter and wash to obtain a "three-cross" wet cake, which is calcined at 600℃ for 2.5h to obtain secondary rare earth exchange microspheres; add 4500g of water and 100g of ammonium phosphate (the mass ratio of ammonium phosphate to NaY zeolite crystallized microspheres is 0.10, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres is 4.5L / g) to the secondary rare earth exchange microspheres), mix evenly, adjust the pH value to 2.8, modify at 85℃ for 1h, filter, wash and dry to obtain a highly active in-situ crystallized catalyst.

[0140] Example 3 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 6000g of water, 1500g of sodium hydroxide solution (Na2O16wt%) and 2500g of 2# kaolin are mixed (the mass ratio of sodium hydroxide to 2# kaolin in the sodium hydroxide solution is 0.124, and the liquid-to-solid ratio of 2# kaolin, sodium hydroxide solution and water is 2.9L / g), and the mixture is reacted at 55°C for 3h, and then kaolin, water glass, silica-alumina activator SA-2 and water are added (the mass ratio of 2# kaolin and kaolin is 1:1, and the mass ratio of the total mass of 2# kaolin and kaolin to water glass and silica-alumina activator SA-2 is 100:6:3) to prepare a modified kaolin slurry with a solid content of 37%, and spray-dry to obtain 4800g of modified kaolin microspheres with a main particle size of 20-150μm, which are recorded as TM2; (2) calcining the modified kaolin microspheres at 780 °C for 4 h to obtain calcined clay balls, denoted as HM2-1; (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystal and silica-alumina activator SA-3 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 1# seed crystal, silica-alumina activator SA-3 and water was 100:350:190:4.8:90:30), and an in-situ crystallization synthesis reaction was carried out at 98°C for 35h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-3. (4) 1000 g of NaY zeolite crystallized microspheres, 450 g of ammonium nitrate and 6500 g of deionized water were mixed (the mass ratio of ammonium nitrate to NaY zeolite crystallized microspheres was 0.45, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 6.5 L / g), the pH value was adjusted to 3.5, exchange was performed at 75 °C for 2 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth nitrate aqueous solution (the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L, and the concentration of rare earth oxides and Na The mass ratio of Y zeolite crystallized microspheres is 0.045, the rare earth elements in rare earth nitrate are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide and cerium oxide in rare earth nitrate is 2:1, the total volume of water in deionized water and rare earth nitrate aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mix evenly, adjust the pH value to 3.8, exchange at 85℃ for 1.5h, filter and wash to obtain the "second exchange" wet cake, calcine at 550℃ for 3h to obtain the primary rare earth exchange microspheres, add Add water and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.045, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 6L / g), mix evenly, adjust the pH value to 3.5, exchange at 90℃ for 1h, filter and wash, and obtain The "three-cross" wet filter cake was calcined at 620°C for 2h to obtain secondary rare earth exchange microspheres; water and 120g of diammonium phosphate were added to the secondary rare earth exchange microspheres (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres was 0.12, and the mass ratio of the volume of water to the mass ratio of NaY zeolite crystallized microspheres was 5L / g), mixed evenly, the pH value was adjusted to 3.2, modified at 90°C for 1h, filtered, washed and dried to obtain a highly active in-situ crystallized catalyst, recorded as JC-2, and the rare earth oxide content was 8.5wt% and P 2.9wt% after analysis.

[0141] Example 4 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 6000g of water, 1500g of sodium hydroxide solution (Na2O16wt%) and 2500g of 2# kaolin are mixed (the mass ratio of sodium hydroxide to 2# kaolin in the sodium hydroxide solution is 0.124, and the liquid-to-solid ratio of 2# kaolin, sodium hydroxide solution and water is 2.9L / g), and the mixture is reacted at 55°C for 3h, and then kaolin, water glass, silica-alumina activator SA-2 and water are added (the mass ratio of 2# kaolin and kaolin is 1:1, and the mass ratio of the total mass of 2# kaolin and kaolin to water glass and silica-alumina activator SA-2 is 100:6:3) to prepare a modified kaolin slurry with a solid content of 37%, and spray-dry to obtain 4800g of modified kaolin microspheres with a main particle size of 20-150μm, which are recorded as TM2; (2) calcining the modified kaolin microspheres at 820 °C for 2 h to obtain calcined clay balls, denoted as HM2-2; (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 2# seed crystal and silica-alumina activator SA-1 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 2# seed crystal, silica-alumina activator SA-1 and water was 100:300:180:2.8:82:45), and an in-situ crystallization synthesis reaction was carried out at 98°C for 24h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-4. (4) 1000 g of NaY zeolite crystallized microspheres, 450 g of ammonium chloride and 6500 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.45, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 6.5 L / g), the pH value was adjusted to 3.5, exchange was performed at 75°C for 2 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth nitrate aqueous solution (the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L, and the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L) were added to the "one-cross" filter cake. The mass ratio of lanthanum oxide to NaY zeolite crystallized microspheres is 0.045, the rare earth elements in rare earth nitrate are lanthanum and cerium, and the mass ratio of lanthanum oxide to cerium oxide in rare earth nitrate is 2:1, and the total volume of water in deionized water and rare earth nitrate aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.8, exchanged at 85℃ for 1.5h, filtered and washed to obtain a "secondary exchange" wet cake, which was calcined at 550℃ for 3h to obtain a primary rare earth exchange Replace the microspheres, add water and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 6L / g), mix well, and adjust the pH value to 3.5, exchange at 90℃ for 1h, filter and wash to obtain "three-cross" wet cake, calcine at 620℃ for 2h to obtain secondary rare earth exchange microspheres; add water and 120g of diammonium phosphate (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres is 0.12, and the volume of water and the mass ratio of NaY zeolite crystallized microspheres is 5L / g) to the secondary rare earth exchange microspheres), mix well, adjust the pH value to 3.2, modify at 90℃ for 1h, filter, wash and dry to obtain a highly active in-situ crystallized catalyst.

[0142] Example 5 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 5500g of water, 750g of sodium hydroxide solution (Na2O16wt%) and 2000g of 2# kaolin was mixed (the mass ratio of sodium hydroxide and 2# kaolin in the sodium hydroxide solution was 0.077, and the liquid-solid ratio of 2# kaolin mixed with the sodium hydroxide solution and water was 3.1 L / g), reacted at 85°C for 1 h, and then halloysite, orthophosphoric acid, water glass, silica-alumina activator SA-3 and water were added (the mass ratio of 2# kaolin and halloysite was 1:1.5, the mass ratio of the total mass of 2# kaolin and halloysite to orthophosphoric acid, water glass and silica-alumina activator SA-3 was 100:1.5:4:12, and the mass ratio of the total mass of 2# kaolin and halloysite to the total mass of orthophosphoric acid and water glass to silica-alumina activator SA-3 was 100:5.5:12), to prepare a modified kaolin slurry with a solid content of 41%, spray dried, and obtained 4700 g of modified kaolin microspheres with a main particle size of 20-150 μm, recorded as TM3; (2) The modified kaolin microspheres were calcined at 770 °C for 3.5 h to obtain calcined clay balls, which were designated as HM3-1. (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystal and silica-alumina activator SA-1 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 1# seed crystal, silica-alumina activator SA-1 and water was 100:280:240:3.5:83:30), and an in-situ crystallization synthesis reaction was carried out at 98°C for 29h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-5. (4) 1000 g of NaY zeolite crystallized microspheres, 350 g of ammonium nitrate and 4500 g of deionized water were mixed (the mass ratio of ammonium nitrate to NaY zeolite crystallized microspheres was 0.35, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 4.5 L / g), the pH value was adjusted to 3.0, and the mixture was exchanged at 85 °C for 2 h. After filtering and washing, a "one-cross" filter cake was obtained; deionized water and a rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides and Na The mass ratio of Y zeolite crystallized microspheres is 0.035, the rare earth elements in rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide and cerium oxide in rare earth chloride is 2:1, the total volume of water in deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.3L / g), mix evenly, adjust the pH value to 3.5, exchange at 90℃ for 1h, filter and wash to obtain a "second exchange" wet cake, calcine at 650℃ for 2h to obtain a primary rare earth exchange microsphere, add water to the primary rare earth exchange microsphere and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 5L / g), mix evenly, adjust the pH value to 3.0, exchange at 90℃ for 1.5h, filter and wash, and obtain "tri- The wet filter cake was calcined at 580°C for 1.5h to obtain secondary rare earth exchange microspheres; water and 90g of ammonium dihydrogen phosphate (the mass ratio of ammonium dihydrogen phosphate to NaY zeolite crystallized microspheres was 0.09, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres was 4.5L / g) were added to the secondary rare earth exchange microspheres, mixed evenly, the pH value was adjusted to 3.5, and the catalyst was modified at 95°C for 1h, filtered, washed and dried to obtain a high-activity in-situ crystallized catalyst, recorded as JC-3, and the rare earth oxide content was 6.5wt% and P 1.9wt% after analysis.

[0143] Example 6 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 5500g of water, 750g of sodium hydroxide solution (Na2O16wt%) and 2000g of 2# kaolin was mixed (the mass ratio of sodium hydroxide and 2# kaolin in the sodium hydroxide solution was 0.077, and the liquid-solid ratio of 2# kaolin mixed with the sodium hydroxide solution and water was 3.1 L / g), reacted at 85°C for 1 h, and then halloysite, orthophosphoric acid, water glass, silica-alumina activator SA-3 and water were added (the mass ratio of 2# kaolin and halloysite was 1:1.5, the mass ratio of the total mass of 2# kaolin and halloysite to orthophosphoric acid, water glass and silica-alumina activator SA-3 was 100:1.5:4:12, and the mass ratio of the total mass of 2# kaolin and halloysite to the total mass of orthophosphoric acid and water glass to silica-alumina activator SA-3 was 100:5.5:12), to prepare a modified kaolin slurry with a solid content of 41%, spray dried, and obtained 4700 g of modified kaolin microspheres with a main particle size of 20-150 μm, recorded as TM3; (2) calcining the modified kaolin microspheres at 810 °C for 2 h to obtain calcined clay balls, denoted as HM3-2; (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 2# seed crystal and silica-alumina activator SA-2 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 2# seed crystal, silica-alumina activator SA-2 and water was 100:330:250:3.8:85:40), and an in-situ crystallization synthesis reaction was carried out at 98°C for 26h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-6. (4) 1000 g of NaY zeolite crystallized microspheres, 350 g of ammonium nitrate and 4500 g of deionized water were mixed (the mass ratio of ammonium nitrate to NaY zeolite crystallized microspheres was 0.35, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 4.5 L / g), the pH value was adjusted to 3.0, exchange was performed at 85°C for 2 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and a rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L) were added to the "one-cross" filter cake. The mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, and the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, and the total volume of water in the deionized water and rare earth chloride aqueous solution and the mass ratio of the NaY zeolite crystallized microspheres is 4.3L / g), mixed evenly, adjusted to a pH value of 3.5, exchanged at 90°C for 1h, filtered and washed to obtain a "second exchange" wet cake, which was calcined at 650°C for 2h to obtain a primary rare earth exchange microsphere. , add water and rare earth chloride aqueous solution to the primary rare earth exchange microspheres (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265 g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 5 L / g), mix well, adjust the pH value to 3.0, Exchange at 90℃ for 1.5h, filter and wash to obtain a "three-cross" wet cake, which is calcined at 580℃ for 1.5h to obtain secondary rare earth exchange microspheres; add water and 90g of diammonium phosphate (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres is 0.09, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres is 4.5L / g) to the secondary rare earth exchange microspheres, mix well, adjust the pH value to 3.5, modify at 95℃ for 1h, filter, wash and dry to obtain a highly active in-situ crystallized catalyst.

[0144] Example 7 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 4800g of water, 400g of sodium hydroxide solution (Na2O16wt%) and 1500g of 2# kaolin was mixed (the mass ratio of sodium hydroxide and 2# kaolin in the sodium hydroxide solution was 0.056, and the liquid-solid ratio of 2# kaolin mixed with the sodium hydroxide solution and water was 3.4 L / g), reacted at 85°C for 1 h, and then halloysite, polyacrylamide, water glass, silica-alumina activator SA-3 and water were added (the mass ratio of 2# kaolin and halloysite was 1.5:3.5, the mass ratio of the total mass of 2# kaolin and halloysite to the mass of polyacrylamide, water glass and silica-alumina activator SA-3 was 100:2:6:8, and the mass ratio of the total mass of 2# kaolin and halloysite to the total mass of polyacrylamide, water glass and silica-alumina activator SA-3 was 100:8:8) to prepare a modified kaolin slurry with a solid content of 43%, spray dried, and obtained 4500 g of modified kaolin microspheres with a main particle size of 20-150 μm, recorded as TM4; (2) calcining the modified kaolin microspheres at 750 °C for 3.5 h to obtain calcined clay balls, which were designated as HM4-1. (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystal and silica-alumina activator SA-3 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 1# seed crystal, silica-alumina activator SA-3 and water was 100:320:230:4.5:78:50), and an in-situ crystallization synthesis reaction was carried out at 98°C for 28h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-7. (4) 1000 g of NaY zeolite crystallized microspheres, 550 g of ammonium chloride and 5500 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.55, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5.5 L / g), the pH value was adjusted to 3.2, exchanged at 90 °C for 2 h, filtered and washed to obtain a "one-cross" filter cake; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides and NaY The mass ratio of zeolite crystallized microspheres is 0.055, the rare earth elements in rare earth chloride are lanthanum and cerium, and the mass ratio of lanthanum oxide and cerium oxide in rare earth chloride is 2:1, and the total volume of water in deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 5.3L / g), mixed evenly, adjusted to pH 3.2, exchanged at 90°C for 1.5h, filtered and washed to obtain a "second exchange" wet cake, calcined at 550°C for 3h to obtain a primary rare earth exchange microsphere, and water was added to the primary rare earth exchange microsphere and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mix evenly, adjust the pH value to 3.2, exchange at 85℃ for 2h, filter and wash, and obtain "tri- The wet filter cake was calcined at 600°C for 1.5h to obtain secondary rare earth exchange microspheres; water and 75g of ammonium dihydrogen phosphate (the mass ratio of ammonium dihydrogen phosphate to NaY zeolite crystallized microspheres was 0.075, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres was 6.5L / g) were added to the secondary rare earth exchange microspheres, mixed evenly, the pH value was adjusted to 3, and the catalyst was modified at 90°C for 1.5h, filtered, washed and dried to obtain a high-activity in-situ crystallized catalyst, recorded as JC-4, and the rare earth oxide content was 4.5wt% and P 1.2wt% were measured by analysis.

[0145] Example 8 The preparation method of the high-activity in-situ crystallization catalyst is as follows: (1) 4800g of water, 400g of sodium hydroxide solution (Na2O16wt%) and 1500g of 2# kaolin was mixed (the mass ratio of sodium hydroxide and 2# kaolin in the sodium hydroxide solution was 0.055, and the liquid-solid ratio of 2# kaolin mixed with the sodium hydroxide solution and water was 3.4 L / g), reacted at 85°C for 1 h, and then halloysite, polyacrylamide, water glass, silica-alumina activator SA-3 and water were added (the mass ratio of 2# kaolin and halloysite was 1.5:3.5, the mass ratio of the total mass of 2# kaolin and halloysite to the mass of polyacrylamide, water glass and silica-alumina activator SA-3 was 100:2:6:8, and the mass ratio of the total mass of 2# kaolin and halloysite to the total mass of polyacrylamide, water glass and silica-alumina activator SA-3 was 100:8:8) to prepare a modified kaolin slurry with a solid content of 43%, spray dried, and obtained 4500 g of modified kaolin microspheres with a main particle size of 20-150 μm, recorded as TM4; (2) calcining the modified kaolin microspheres at 830 °C for 2 h to obtain calcined clay balls, which were designated as HM4-2; (3) The calcined clay ball was mixed with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystal and silica-alumina activator SA-3 (the mass ratio of calcined clay ball, water glass, sodium hydroxide solution, 1# seed crystal, silica-alumina activator SA-3 and water was 100:270:210:4.4:79:40), and an in-situ crystallization synthesis reaction was carried out at 98°C for 31h. The mixture was filtered, washed and dried to obtain NaY zeolite crystallized microspheres, which were recorded as JM-8. (4) 1000 g of NaY zeolite crystallized microspheres, 550 g of ammonium chloride and 5500 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.55, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5.5 L / g), the pH value was adjusted to 3.2, exchanged at 90 °C for 2 h, filtered and washed to obtain a "one-cross" filter cake; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L) were added to the "one-cross" filter cake. The mass ratio of oxide to NaY zeolite crystallized microspheres is 0.055, the rare earth elements in rare earth chloride are lanthanum and cerium, and the mass ratio of lanthanum oxide to cerium oxide in rare earth chloride is 2:1, and the total volume of water in deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 5.3L / g), mixed evenly, adjusted to pH 3.2, exchanged at 90°C for 1.5h, filtered and washed to obtain a "second exchange" wet cake, which was calcined at 550°C for 3h to obtain a primary rare earth exchange microsphere. , add water and rare earth chloride aqueous solution to the primary rare earth exchange microspheres (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mix well, and adjust the pH value to 3. 2. Exchange at 85°C for 2h, filter and wash to obtain a "three-cross" wet filter cake, which is calcined at 600°C for 1.5h to obtain secondary rare earth exchange microspheres; add water and 75g of diammonium phosphate (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres is 0.075, and the volume of water to the mass ratio of NaY zeolite crystallized microspheres is 6.5L / g) to the secondary rare earth exchange microspheres), mix evenly, adjust the pH value to 3, modify at 90°C for 1.5h, filter, wash and dry to obtain a highly active in-situ crystallized catalyst.

[0146] Comparative Example 1 (1) According to Example 1 of patent CN1778676A, SM-1 kaolin spray balls were prepared, Example 4 was used to prepare calcined balls SC1-2 and SP1-2, and Example 7 used SC1-2 and SP1-2 to prepare crystallized microspheres DJM; (2) Mix 1000 g of crystallized microspheres DJM, 550 g of ammonium chloride and 5500 g of deionized water (the mass ratio of ammonium chloride to crystallized microspheres DJM is 0.55, and the mass ratio of the volume of water to the crystallized microspheres DJM is 5.5 L / g), adjust the pH value to 3.2, exchange at 90 °C for 2 h, filter and wash to obtain a "one-cross" filter cake; add deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution is 265 g / L, and the mass ratio of rare earth oxides to crystallized microspheres DJM is 5.5 L / g) to the "one-cross" filter cake. The mass ratio of lanthanum oxide to cerium oxide in rare earth chloride is 2:1, and the mass ratio of the total volume of water in the deionized water and rare earth chloride aqueous solution to the crystallized microsphere DJM is 5.3L / g), mixed evenly, adjusted to pH 3.2, exchanged at 90℃ for 1.5h, filtered and washed to obtain a "second exchange" wet cake, calcined at 550℃ for 3h to obtain a primary rare earth exchange microsphere, and water and chlorine were added to the primary rare earth exchange microsphere. The rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to crystallized microspheres DJM is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of crystallized microspheres DJM is 4.5L / g), mixed evenly, adjusted the pH value to 3.2, exchanged at 85℃ for 2h, filtered and washed, The "three-cross" wet filter cake was obtained and calcined at 600°C for 1.5h to obtain secondary rare earth exchange microspheres; water and 75g of diammonium phosphate were added to the secondary rare earth exchange microspheres (the mass ratio of diammonium phosphate to crystallized microspheres DJM was 0.075, and the mass ratio of the volume of water to the crystallized microspheres DJM was 6.5L / g), mixed evenly, the pH value was adjusted to 3, modified at 90°C for 1.5h, filtered, washed and dried to obtain a catalyst, recorded as DC, and the rare earth oxide content was measured to be 4.4wt% and P 1.3wt% after analysis.

[0147] The XRD pattern of NaY zeolite crystallized microspheres JM-6 prepared in step (3) of Example 6 is as follows: Figure 1 As shown, its SEM image is Figure 2 The SEM image of its surface is shown in Figure 3 shown.

[0148] The XRD pattern of the crystallized microsphere DJM prepared in step (1) of comparative example 1 is as follows: Figure 4 As shown, its SEM image is Figure 5 The SEM image of its surface is shown in Figure 6 shown.

[0149] The parameters of the in-situ crystallization synthesis reaction in Examples 1 to 8 and Comparative Example 1 and the crystallinity and silicon-aluminum ratio of the prepared crystallized microspheres are shown in Table 1.

[0150] Table 1 Parameters of in-situ crystallization synthesis reaction and crystallinity and silicon-aluminum ratio of prepared crystallized microspheres in Examples 1 to 8 and Comparative Example 1

[0151] It can be seen from Table 1 that the crystallized microspheres prepared by the present invention have higher crystallinity and higher silicon-aluminum ratio.

[0152] Metal contamination experiments were conducted on the catalysts prepared in Examples 1, 3, 5, 7 and Comparative Example 1 to compare and analyze the differences in their ability to resist metal contamination. JC-1 to JC-4 and DC catalysts were contaminated with V 8000ppm and Ni 4000ppm, respectively, and aged for 4 hours at 800°C and 100% steam; at the same time, the uncontaminated catalyst was aged for 17 hours at 800°C and 100% steam, and then the micro-reactivity of the aged catalysts was tested. The micro-activity data of the catalysts before and after metal contamination are listed in Table 2.

[0153] Table 2 Comparison of micro-reaction activity before and after metal contamination

[0154] It can be seen from Table 2 that, compared with the comparative catalyst DC, the catalyst of the present invention has higher micro-reaction activity and metal contamination activity retention rate.

[0155] Application Examples The reaction effects of the catalysts prepared in Examples 1, 3, 5, 7 and Comparative Example 1 of the present invention were described using a fixed fluidized bed reaction evaluation device. The JC-1~JC-4 and DC catalysts were treated at 800°C and 100% steam for 17 hours, and then cracked in an ACE (Advanced Catalytic Evaluation) fixed fluidized bed reactor. The reaction conditions were a catalyst loading of 9 g, a catalyst-to-oil ratio of 6, a reaction temperature of 527°C, and a weight space velocity of 8 h. -1 The properties of the raw oil are shown in Table 3, and the catalytic results are shown in Table 4.

[0156] Table 3 Properties of feedstock oil for ACE reaction

[0157] Table 4 Distribution of reaction products and catalyst performance in application examples

[0158] Total liquid intake refers to: liquefied gas + gasoline + diesel.

[0159] As can be seen from Table 4, compared with the comparative catalyst DC, the catalyst provided by the present invention has higher heavy oil conversion capacity and target product yield (total liquid yield, gasoline), showing excellent catalytic reaction performance.

[0160] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a highly active in-situ crystallization catalyst, characterized in that: The following steps are involved: (1) mixing kaolin with alkali solution and water, adding kaolin, silicon-aluminum activator and dispersant after alkali treatment to obtain modified kaolin slurry, and spray drying to obtain modified kaolin microspheres; (2) calcining the modified kaolin microspheres obtained in step (1) to obtain calcined kaolin microspheres; (3) mixing the calcined soil balls obtained in step (2) with water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-aluminum activator to carry out an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (4) mixing the NaY zeolite crystallized microspheres obtained in step (3) with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (5) mixing the ammonium salt exchange microspheres obtained in step (4) with a rare earth salt and water, and sequentially performing a first rare earth exchange and a first calcination to obtain primary rare earth exchange microspheres; (6) mixing the primary rare earth exchange microspheres obtained in step (5) with rare earth salt and water, and sequentially performing a second rare earth exchange and a second calcination to obtain secondary rare earth exchange microspheres; (7) The secondary rare earth exchange microspheres obtained in step (6), water and a phosphorus compound or a boron compound are mixed and modified to obtain a highly active in-situ crystallization catalyst.

2. The preparation method according to claim 1, characterized in that: The alkali solution in step (1) includes a sodium hydroxide solution; the mass ratio of sodium hydroxide to kaolin in the sodium hydroxide solution is 0.02-0.

25.

3. The preparation method according to claim 1, characterized in that: The temperature of the alkali treatment in step (1) is 30-95° C., and the time of the alkali treatment is 0.5-10 h.

4. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of kaolinite to kaolin is (1-5): (1-6); the mass ratio of the total mass of kaolinite and kaolin to the mass of the silica-alumina activator and the dispersant is 100: (0.5-12): (2-12).

5. The preparation method according to claim 1, characterized in that: The calcination temperature in step (2) is 700-900° C. and the calcination time is 1-5 hours.

6. The preparation method according to claim 1, characterized in that: The temperature of the in-situ crystallization synthesis reaction in step (3) is 90-110° C., and the time of the in-situ crystallization synthesis reaction is 16-40 hours.

7. The preparation method according to claim 1, characterized in that: In the step (4), the pH value of the ammonium salt exchange is 2.5-4, the temperature of the ammonium salt exchange is 30-100° C., and the time of the ammonium salt exchange is 0.5-4 h.

8. The preparation method according to claim 1, characterized in that: The pH value of the modification treatment in step (7) is 2.5-4, the temperature of the modification treatment is 40-100° C., and the time of the modification treatment is 0.5-4 h.

9. A high-activity in-situ crystallization catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high-activity in-situ crystallization catalyst according to claim 9 in catalytic cracking of heavy oil.

Citation Information

Patent Citations

  • Preparation method of modified catalyst

    CN102921449A

  • Preparation method of in-situ crystallization catalytic cracking catalyst

    CN110523429A

  • Preparation method of modified Y-type molecular sieve

    CN111686784A

  • Catalytic cracking catalyst as well as preparation method and application thereof

    CN113318779A

  • All-white clay catalyst for fluid catalytic cracking and its preparation

    CN1232862A

Cited By

  • NaY zeolite in-situ crystallization microsphere with high silica-alumina ratio as well as preparation method and application of NaY zeolite in-situ crystallization microsphere

    CN121405106A